(untitled) (Advances in Applied Biological Research, 2026)
Zinc oxide/copper (ZnO/Cu) nanoparticles were synthesized using a green synthesis method based on pomegranate pulp peel extract. The purpose of the study is to manufacture an environmentally friendly zinc and copper oxide nanocomposite using plant residues from pomegranate pulp peel extract, and to use it to combat bacterial blight in tomatoes. The synthesized sample was examined to characterize the nanoparticles using UV-Vis spectroscopy, energy dispersive spectroscopy (EDS), field-emission scanning electron microscopy (FE SEM), and X-ray diffraction (XRD).The observed peak at 480 nm in the surface plasmon resonance of the zinc oxide nanoparticles indicated the formation of nanoparticles of varying sizes, both large and small. The successful synthesis of the compound was inferred from the shift in the UV-Vis absorption peaks using pH, time, concentration, copper-to-zinc oxide ratio, and temperature. X-ray diffraction (XRD) and phase morphology analysis revealed the crystalline nature of the nanoparticles. The average crystal size of the ZnO nanoparticles synthesized using the extract and ZnO/Cu nanocomposites was 24.16 nm, representing the highest point in the halo. However, this is not considered a sharp “crystalline peak,” and the presence of sharp peaks at angles of 25.85, 29.45, and 31.85 is strong evidence of a regular atomic arrangement. Morphological analysis of the synthesized nanoparticles using high-resolution electron microscopy (HR-TEM) revealed an irregular to nearly spherical shape with sizes ranging from 10 to 200 nm.